UPAYA MENINGKATKATKAN HASIL BELAJAR MATA PELAJARAN BAHASA INDONESIA MATERI BIJAK MEMAKAI UANG MELALUI MODEL ROLE PLAYING PADA MURID KELAS II SD NEGERI SUKUN 2 KOTA MALANG - Firdani Arifianda, Erizka; Andika Gutama; Ahmad Rifki Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This Classroom Action Research (CAR) aims to improve the learning outcomes of second-grade students of Sukun 2 Elementary School, Malang City, in the Indonesian Language subject "Wise Use of Money" through the application of the Role Playing learning model. The main problems in this study are the low focus on learning, the activities of male students who tend to be less conducive, and classical cognitive learning outcomes that have not met the Minimum Completion Criteria (KKM). The research approach used is descriptive quantitative to measure the improvement in student learning outcomes. The study was conducted in two cycles using the Kemmis & McTaggart model which includes the planning, implementation, observation, and reflection stages. The research subjects were 29 second-grade students of Sukun 2 Elementary School, Malang City, consisting of 12 male students and 17 female students. Data collection instruments were learning outcome tests (cognitive evaluation) and student activity observation sheets. The results of the study showed a significant increase in classical learning outcomes. In the pre-cycle conditions, students' classical completion was 34.48%. After the interventions in Cycle I, the classical completion rate increased to 62.07%, and at the end of Cycle II, it jumped dramatically to 89.65%, with a class average score of 79.31. Thus, the implementation of the Role-Playing learning model has been quantitatively proven to be effective in improving learning outcomes in financial literacy in elementary schools.